(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Pineapple (Ananas comosus (L.) Merr. ’Prabumulih’) is a tropical fruit that is very popular for its unique aroma and sweet taste. It is also commonly believed that this fruit has potential applications in traditional medicine. However, the peel is not fully harnessed, despite its rich and intricate composition. This study presented findings regarding the endophytic fungi discovered within the peel of A comosus (L.) Merr. ’Prabumulih’ and their performance as antioxidants. The endophytic fungal species were identified based on their morphological characteristics. The antioxidant assessment was carried out using the DPPH method. According to the findings of morphological identification, Trichoderma harzianum, an endophytic fungus, was found to exhibit the highest potential as an antioxidant source. Antioxidant activity showed a very strong category (IC50 = 18.74 µg/mL). Through the isolation of its pure constituents and subsequent in vivo testing, there is the potential for this extract from the endophytic fungus to evolve into an innovative source of antioxidants.